Antimicrobial and antifungal activity of new fluorophenyl-containing 1,2,4-triazoles - O. A. Bihdan (The State Expert Center of the Ministry of Health of Ukraine, 2021)
The achievements of the world organic chemistry are most clearly represented by scientific publications that prove the promising nature of heterocyclic substances. The possibility of combining various pharmacophore fragments and 1,2,4-triazole in one molecule is quite popular. In 2018, the drug Trifuzol-NEO appeared on the veterinary market of Ukraine, which took its rightful place among synthetic immunomodulators for various groups of unproductive animals. So, further studies of new promising compounds among substituted 1,2,4-triazole, which can be used as objects for the creation of new original domestic antimicrobial and antifungal agents, remains relevant and has theoretical and practical significance. The aim of our work was to investigate the antimicrobial and antifungal activity of a number of new fluorophenyl-containing derivatives of 1,2,4-triazole and, in some cases, to trace the presence of certain patterns between structure and action. The sensitivity of new fluorophenyl-containing derivatives of 1,2.4-triazole was studied by the method of serial dilutions in accordance with the methodological recommendations. From the initial concentration of the new synthesized compounds of 1 mg/ml, a series of two-fold serial dilutions were prepared in Mueller-Hinton broth in a volume of 1 ml. Then, 0.1 ml of microbial curtain (106 m. c./ml) was added to each tube. MIC (MIC) was determined in the absence of visible growth in a test tube with the minimum concentration of the drug, the minimum bactericidal concentration (MBcK) - in the absence of growth on agar after inoculation from transparent tubes. Dimethyl sulfoxide was used as a solvent for the compounds in the studies. The research was carried out at the Department of Microbiology, Virology and Immunology of Zaporizhzhia State Medical University. Analyzing the results of studying the sensitivity of substances to Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, it should be noted that almost all compounds were active against the bacteria. It should be noted that a number of compounds were found to be the most active against Staphylococcus aureus, and 5-(2-fluorophenyl)-4-(((5-nitrofuran-2-yl)methylene)amino-4H-1,2,4-triazole-3-thiols generally exceeded several times the activity indices of the reference drug (MIC 1.95 μg/ml, MBcK 3.9 μg/ml) to Staphylococcus aureus. Most of the compounds were found to be quite active against Candida albicans. Among the corresponding 5-(2-fluorophenyl)-4-((aryl)ylidene)amino-1,2,4-triazole-3-thiols, the highest activity for Candida albicans exhibit 5-(2-fluorophenyl) -4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol and 5-(2-fluorophenyl)-4-((2,3-dimethoxyphenyl)ylidene)amino-1,2,4-triazole-3-thiol. It was found that most of the compounds exhibit a moderate antimicrobial and a fairly high antifungal effect. The most sensitive strain was S. aureus in relation to 5-(2-fluorophenyl)-4-(((5-nitrofurans-2-yl)methylene)amino-4H-1,2,4-triazole-3-thiol, Candida albicans proved to be very sensitive to 5-(2-fluorophenyl)-4-((4-bromophenyl)ylidene)amino-1,2,4-triazole-3-thiol and 5-(2-fluorophenyl)-4((2,3-dimethoxyphenyl)ylidene)amino-1,2,4-triazole-3-thiol.